Acceleration of digital transformation as a result of launching programs financed from public funds: Assessment of the implementation of the operational program digital Poland - Miroslaw Moroz (Foundations of Management, 2018)
The main purpose of the paper is to assess the current implementation of the Operational Program Digital Poland in terms of coherence with the trends of digital transformation. The Operational Program Digital Poland (OPDP) is one of the programs financed from public funds, which is directly targeted at the development of the digital economy in Poland. At the end of 2017, the implementation of the program is at the halfway point, which gives the premise to reflect on the degree of convergence of goals and program implementation with the trends of digital transformation. The research methodology is based on the analysis of secondary sources and participant observation. The results of the analysis show that the results of actions undertaken under the OPDP in principle indirectly contribute to the progressing trend of digitization of the Polish economy. The structure of expenditures under the OPDP testifies to the relative shallow rooting of the digital transformation or, more broadly, the digital economy in Poland.
Keywords: 650; digital transformation; Operational Program Digital Poland; Public structural expenditure; Poland